Metagenome Analysis of a Complex Community Reveals the Metabolic Blueprint of Anammox Bacterium “Candidatus Jettenia asiatica” - Hu, Ziye; Speth, Daan R.; Francoijs, Kees-Jan; Quan, Zhe-Xue; Jetten, Mike (Frontiers in Microbiology, 2012)
Anammox bacteria are key players in the global nitrogen cycle and responsible for up to 50% of global nitrogen loss. Because of their cost effective application in anaerobic nitrogen removal, the anammox bacteria are widely implemented in wastewater treatment. Currently, five genera of anammox bacteria have been identified, together forming a deep branching order in the Planctomycetes-Verrucomicrobium- Chlamydiae (PVC) superphylum. Members of all genera have been detected in wastewater treatment plants, but metagenomic information is not yet available for all genera. Here we report the metagenomic analysis of an enrichment dominated by ‘Candidatus Jettenia asiatica’. The whole microbial community o f a granular sludge anammox reactor was sequenced using both illumina and 454 pyrosequencing. The sludge was previously shown to have a ~50% enrichment of the anammox bacterium ‘Candidatus Jettenia asiatica’ by 16S rRNA gene analysis. After de novo assembly 37,432 contigs with an average length of 571 nt were obtained. The contigs were then analyzed by BLASTx searches against the protein sequences of ‘Candidatus Kuenenia stuttgartiensis’ and a set of 25 genes essential in anammox metabolism were detected. Additionally all reads were mapped to the genome of an anammox strain KSU-1 and de novo assembly was performed again using the reads that could be mapped on KSU-1. Using this approach, a gene encoding copper-containing nitrite reductase NirK was identified in the genome, instead of cytochrome cd1-type nitrite reductase NirS that is responsible for the nitrite reduction of ‘Ca. Kuenenia stuttgartiensis’ and ‘Ca. Scalindua profunda’. Finally, the community composition was investigated through MetaCluster analysis, 16S rRNA gene analysis and read mapping, which showed the presence of other important community members such as aerobic ammonia-oxidizing bacteria, methane producing microorganisms and denitrifying methanotroph 'Ca. Methylomirabilis oxyfera'.